Clinical and laboratory characteristics and results of treatment of patients with ACTH-producing neuroendocrine tumors of various localization - Olga O. Golounina ("Consilium Medicum" Publishing house, 2021)
Aim. To study the clinical, biochemical characteristics, treatment results and follow-up of patients with ectopic ACTH syndrome EAS (ACTH adrenocorticotropic hormone ).